Social Media And Moral Panic: Examining The Case Of Antis Fandom On Social Media X - Jasmine Aina Salsabila; Iqrak Sulhin (Green Publisher Indonesia, 2024)
The belief that consuming violent media will lead someone to commit violence is a longstanding societal concern. This concern manifests in the phenomenon of 'antis' within fandoms, which began to emerge around 2016. Initially driven by shipping conflicts, the issue of social justice and the increasing use of social media have allowed this phenomenon to spread easily across various fandoms worldwide. Antis' behavior can be seen as a form of moral panic in several ways: by associating pro-shippers—those who do not agree that consuming violent content will turn someone into a perpetrator or supporter of violence—with sexual offenders and pedophiles, antis use an 'us versus them' mentality to uphold their moral standards and portray themselves as the most moral group.